The black summer bushfires: impacts and risk factors for livestock bushfire injury in south‐eastern Australia. Issue 7 (5th May 2022) - Cowled, BD; Hillman, A; Ward, MP; Clutterbuck, H; Doyle, M; Webb Ware, J; Thomas, M; Plain, K; Barwell, R; Laurence, M; Pfeiffer, C
Abstract : Background: The 2019/2020 Australian bushfires were the largest bushfire event in modern Australian history. While actions to mitigate risk to homes from bushfires are well reported, there is very little research reported on the impacts of bushfires on livestock. With an increasing incidence of bushfires predicted, there is an urgent need to identify how farmers can best protect their livestock. Objectives: Compare bushfire affected farms with and without injured livestock to identify associations between risk factors and bushfire injury. Infer management approaches that can be used to reduce bushfire injury in livestock. Method: A case‐control study using a structured interview questionnaire, delivered in late 2020 to cattle and sheep farmers in south‐eastern Australia (New South Wales and Victoria) whose farmland was burnt in the 2019/2020 Australian bushfires. Case farms were farms with bushfires injured or killed livestock. Control farms were farms that had no bushfire injured livestock but that still had fire present on the farm. Interview responses were summarised and information theoretical approaches were used to identify potential risk factors for livestock bushfire injury and protective actions that could inform future fire‐preparation recommendations. Results and discussion: Of 46 farms in the case‐control study, 21 (46%) reported bushfire injured or killed livestock. Apparent protective factors identified included: preparation (having a bushfire plan and more than two farm bushfire fighting units), backburning and receiving assistance from fire authorities. Combined beef and sheep grazing enterprises appeared to have an increased risk of bushfire injury to livestock.